Total Quality Character Education (TQCE) in Pesantren Life: an Auto-ethnographic Journey - Ubaidillah, Aan Fardani; Fika Fitriasari (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
This study explores how the principles of Total Quality Management (TQM) are internalized and interpreted as Total Quality Character Education (TQCE) within pesantren life. Using an autoethnographic method, the researchers reflect on personal experiences as a student and administrator in two Indonesian pesantren, examining the formation of character through daily discipline, peer leadership, and symbolic guidance from the kyai. The data were gathered through reflexive journaling, document analysis, and embedded interactional notes, then analyzed using Spradley’s 12-step ethnographic framework. The research revealed that TQCE is not only a character education model but also a lived culture grounded in ritual consistency (standardization), collective governance (peer accountability), and moral exemplarity (kyai leadership). Routines such as tahajjud, musyawarah, and muhasabah served as formative practices shaping discipline and responsibility. Peer mentoring fostered collective responsibility, while the kyai’s symbolic leadership became the spiritual anchor guiding values and behaviors. This study concludes that TQCE integrates the procedural strength of TQM with the spiritual-cultural fabric of pesantren, offering a sustainable framework for holistic character formation.